Proteomic Analysis of the Protective Effect of Eriodictyol on Benzo(a)pyrene-Induced Caco-2 Cytotoxicity - Wang, Chong; Zhao, Fan; Bai, Yun; Li, Chunbao; Xu, Xinglian; Kristiansen, Karsten; Zhou, Guanghong (Frontiers in Nutrition, 2022)
We evaluated the possible protective effects of six polyphenols on benzo(a)pyrene (BaP)-induced cytotoxicity in Caco-2 cells. We show that treatment with quinic acid, ferulic acid, homovanillic acid, trolox and BaP decreased cell viability, whereas naringenin and eriodictyol affected viability in a bi-phasic manner with low concentrations decreasing viability whereas higher concentrations increase viability. Co-treatment with 20 µM eriodictyol or naringenin reduced BaP-induced cytotoxicity, including cell apoptosis, cell cycle progression, and oxidative stress. Our results show that the protective effect of eriodictyol was superior to that of naringenin. The potential protective mechanisms of eriodictyol on BaP-induced toxicity were investigated by proteomics. We identified 80 differentially expressed proteins (DEPs) with proteins associated with genetic information processing pathway representing the highest proportion and number of proteins responding to eriodictyol treatment, including key proteins such as RPA2, SNRPA, RAD23B, NUP155 and AARS. Our results provide new knowledge on how polyphenols may prevent BaP-induced carcinogenesis.